In Bundelkhand... Ensuring livelihood security through organic farming - Ram, R A (Indian Horticulture, 2019)
Organic farming technology was disseminated in NHB funded programme in Azamgarh and Bundelkhand region of Uttar Pradesh. Farmers were trained for on-farm production of quality organic inputs with locally available materials. Initially, 60 farmers in each district were trained for organic production of medicinal and aromatic crops. Seeing the success and income of farmers, more than 2,000 farmers in Azamgarh, Hamirpur and Mahoba districts of Uttar Pradesh have adopted cultivation of medicinal and aromatic crops. Farmers’ fields have been group certified and farm produces are being purchased backed by different firms for export purpose. Approximately 8,000 ha area is covered under organic production of various crops.